Identification of Lactic Acid Bacteria (LAB) Consortium from Tempeh Jember Based on 16S rRNA Gene Sequences as Potential Probiotic Candidates - Siti Nur Azizah; Rosida Rosida; Rizka Yolanda Febiaocti; Dewi Riskha Nurmalasari; Sipriyadi Sipriyadi (Biology, Medicine, & Natural Product Chemistry, 2025)
The development of pharmaceutical raw materials as local Indonesian probiotic concentrates requires attention to strain identity accuracy, safety, and health potential. This is due to the high potential of probiotics in preventing and addressing various health disorders from infancy to old age. Previous research successfully obtained lactic acid bacteria (LAB) isolates as probiotic candidates from tempeh produced in Jember, and preclinical testing showed that administering a consortium of five LAB isolates at a dose of 10^8 CFU/ml to BALB/c mice was an effective treatment for further application. This study aimed to perform molecular identification of the consortium of five LAB isolates from tempeh in Jember, East Java, based on 16S rRNA gene sequences. The consortium includes TA1, TB1, TK1, TK2, and TK4 isolates. This study used both qualitative descriptive and quantitative methods. Identification based on the 16S rRNA gene to determine LAB species strains involved bacterial genomic DNA isolation, amplification of the bacterial 16S rRNA gene, PCR product analysis, and phylogenetic identification and analysis. DNA amplification results showed that the consortium of five LAB isolates produced DNA fragments with bands of approximately 1300 bp. BLAST-N and phylogenetic analysis of the 16S rRNA gene showed that TB1 had 99.05% similarity with Kosakonia cowanii JCM 10956, TA1 had 99.46% similarity with Lactiplantibacillus plantarum JCM 1149, TK1 had 99.38% similarity with Lactiplantibacillus pentosus 124-2, TK2 had 96.86% similarity with Pseudomonas fluvialis ASS-1, and TK4 had 99.38% similarity with Lactiplantibacillus plantarum NBRC 15891. TA1, TB1, and TK4 were identified as non-pathogenic LAB strains, while TK1 and TK2 were not classified as LAB.